Prehospital Initiation of Buprenorphine Treatment for Opioid Use Disorder by Paramedics. (2nd November 2022) - Hern, H. Gene; Goldstein, David; Kalmin, M.; Kidane, S.; Shoptaw, S.; Tzvieli, Ori; Herring, Andrew A.
Abstract : Prehospital initiation of buprenorphine treatment for Opioid Use Disorder (OUD) by paramedics is an emerging potential intervention. Many patients who may be at high risk for overdose deaths may never engage in treatment because they frequently refuse transport. Recent data have demonstrated a significant increase in both short and long term mortality following an opioid overdose. We describe 3 preliminary cases with a novel intervention of initiating Buprenorphine in the prehospital setting for symptoms of opioid withdrawal, regardless of etiology. In addition, we describe tracking of long term engagement in additional services as part of an integrated approach to combatting the opioid epidemic through EMS focused interventions.